Gender differences in the association between metabolic syndrome and periodontal disease: the Hisayama Study. (8th July 2013) - Furuta, Michiko; Shimazaki, Yoshihiro; Takeshita, Toru; Shibata, Yukie; Akifusa, Sumio; Eshima, Nobuoki; Kiyohara, Yutaka; Ninomiya, Toshiharu; Hirakawa, Yoichiro; Mukai, Naoko; Nagata, Masaharu; Yamashita, Yoshihisa
Abstract Aims Periodontal disease and metabolic syndrome (MS) are more prevalent in males than in females. However, whether there is a gender difference in the association between these health conditions has not yet been investigated. This study examined the gender difference in this association, considering the definition of periodontal disease. Materials and Methods We recruited 1040 males and 1330 females, aged ≥40 years, with at least ten teeth from subjects of the 2007 Hisayama health examination. We performed a logistic regression analysis with various definitions of periodontal disease the dependent variable and MS as the independent variable. Following the analysis, the data were reanalysed with the structural equations model. Results The logistic regression analysis suggested a stronger association between periodontal disease and MS in females than that in males when periodontal disease was more severely defined. When we constructed the structural equations model in each gender, the model showed a good fit to the data of females, suggesting the association between periodontal disease and MS in females, but not in males. Conclusions Gender differences seem to exist in the association between periodontal disease and MS; MS might show a stronger association with periodontal disease in females than in males.